The Prognostic and Immune Significance of BZW2 in Pan-Cancer and its Relationship with Proliferation and Apoptosis of Cervical Cancer - Chaolin Li; Qin Li; Li Li; Siyu Sun; Xun Lei (Frontiers in Bioscience-Landmark, 2024)
Background: Basic leucine zipper and W2 domains 2 (BZW2), a member of the basic domain leucine zipper superfamily of transcription factors, has been implicated in the development and progression of various cancers. However, the precise biological role of BZW2 in pan-cancer datasets remains to be explored. This study aimed to assess the prognostic significance of BZW2 and its immune-related signatures in various tumors. Methods: Our study investigated the expression, epigenetic modifications, and clinical prognostic relevance of BZW2 using multi-omics data in different cancer types. Additionally, the immunological characteristics, tumor stemness, drug sensitivity, and correlation of BZW2 with immunotherapy response were explored. Finally, in vitro experiments were conducted to assess the impact of BZW2 knockdown on Hela cells, a cell line derived from cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC). Results: BZW2 exhibited elevated expression levels in various tumor tissues and significantly impacted the prognosis of different cancer types. BZW2 emerged as an independent prognostic factor in CESC. We found that copy number amplification and methylation levels of BZW2 were associated with its mRNA expression. Immunological analyses revealed that BZW2 shapes a non-inflamed immunosuppressive tumor microenvironment across multiple cancers. Furthermore, our cell experiments demonstrated that BZW2 knockdown reduced proliferation, migration, and apoptosis activities in CESC cells. Conclusions: BZW2 promotes cancer progression by shaping a non-inflamed immunosuppressive tumor microenvironment. Additionally, BZW2 was shown to significantly influence the proliferation, migration, and apoptosis of CESC cells.